1931 Cal. Stat. 2316-17 - (:unkn) unknown (My University, 1931)
Ch. 1098, § 1: Prohibited noncitizens, felony convicts, or drug addicts from owning, possessing, or having under their custody or control any pistol, revolver, or concealable firearm; violators subject to fine or imprisonment.
Keywords: POSSESSION - DANGEROUS PERSONS